Redesain Instalasi Listrik Dikantor Pusat Universitas Sam Ratulangi - Alfano B.C. Dien; Vecky C. Poekoel; Martinus Pakiding (Jurnal Teknik Elektro dan Komputer, 2018)
Abstractâ€”Problems in electrical installation are still widely found in the field, in the Rektorat Building of UNSRAT found probles in the installation of electrical installation, such as the neatness of the electrical installation path and the setting in the Rektorat building. This problems can not be shared, so the power obtained can not be utilized as it should be. Recognized with the problems of electric power installation in the faculty of engineering I took the title oft thesis â€œRedesing Electric Power installation in the Rektorat Building Sam Ratulangi Universityâ€. From my research on electrical installation in the main buildings of Rektorat, found the division in the main building Rektorat not per floor erratic. Keywords : Development; Electric Power Installation; Rektorat building UNSRAT; Structuring.Abstrakâ€”Masalah dalam instalasi tenaga listrik masih banyak ditemukan dilapangan, di gedung rektorat unsrat ditemukan masalah dalam pemasangan instalasi listrik yang dilakukan, antara lain masalah kerapihan jalur instalasi listrik, dan pengaturan pembagian beban di gedung Rektorat, masalah ini mengakitbatkan pembagian tiap fasa tidak seimbang sehingga daya yang didapat tidak dapat di manfaatkan sebagai mana mestinya. Berdasarkan dengan masalah instalasi tenaga listrik di Rektorat saya mengambil judul skripsi â€œ Redesain Instalasi Listrik Dikantor Pusat Universitas Sam Ratulangiâ€. Dari penelitian yang saya lakukan terhadap masalah instalasi listrik.Kata kunciâ€” Gedung Rektorat Â UNSRAT; Instalasi Tenaga Listrik; Penataan; Pengembangan.